The impact of selected macroeconomic variables towards economic growth in 3 developing ASEAN countries / Abdul Hakkim Mat Johari - Mat Johari, Abdul Hakkim (2016)
This study is work on the impacts of selected macroeconomic variables towards economic growth in three developing ASEAN countries which are Malaysia, Thailand, and Indonesia over the period 2005 to 2014. The OLS regression was used to find the impact of selected macroeconomics variables towards economic growth and the relationship between those variables (FDI, inflation rate and interest rate) with the economic growth. The result concludes that FDI gives the most significant relationship towards economic growth compare with the inflation and interest rate. Besides, only two variables are significant towards economic growth which is FDI and inflation rate meanwhile interest rate is not significant towards economic growth. FDI and inflation have a positive relationship with economic growth while interest rate has a negative relationship with economic growth. These studies recommend some policy and alternative to enhance the economic growth in those countries.